Rentabilidade econômica de três regimes de manejo de Pinus taeda L., em Dionísio Cerqueira – SC - Cruz, Maurício Ivan (2021)
The world has a total forest area of 4.06 billion hectares, but this area is decreasing annually. This leads to worldwide environmental impacts that require an immediate response. One of the most efficient actions is to increase the area of planted forests and adopt management strategies and silvicultural techniques for forest restoration and use of wood. The main objective of this study was to evaluate three types of forest management for a Pinus taeda stand in a property located in Dionísio Cerqueira, in the extreme northwest of Santa Catarina. Proposal 1 evaluated the financial return from the sale of wood for mechanical processing, proposal 2 evaluated the financial return for a 7-year-old forest, allocating the wood for energy in the form of wood chips and firewood, and proposal 3 evaluated the financial return of the population at 15 years of age for mechanical and energy processing. For this purpose, the forest inventory of the stand was made and, with the raised dendrometric parameters, the hypsometric, volumetric, tapering and assortment relations of the forest stand were calculated. Also, using the SisPinus software, the forest stand was simulated for the three studied proposals. These proposals were analyzed economically using the Net Present Value (NPV), the Internal Rate of Return (IRR) and the Benefit-Cost Ratio (B/C). For the results found, the forest stand has a timber volume of 506.97 m³ / ha or 5272.46 m³ in its entire area. The SisPinus software accurately simulated the studied population, presenting an estimate error of 1.78%. It is concluded that proposals 1 and 2 are economically unfeasible, presenting a NPV of, respectively, R$ -4,436.49 and R$ - 38,421.47. Proposal 3 was considered economically viable, with its NPV of R$ 11,463.38.